1998
DOI: 10.1103/physrevlett.80.3288
|View full text |Cite
|
Sign up to set email alerts
|

Activation Volume ofC57oDiffusion in AmorphousCo81

Abstract: We have measured the pressure and temperature dependence of 57 Co diffusion in structurally relaxed Co 81 Zr 19 glass. The activation enthalpy and the preexponential factor are 1.4 eV and 8.4 3 10 29 m 2 s 21 . The pressure dependence is extremely small and yields an activation volume of V act ͑0.08 6 0, 1͒V, where V is the mean atomic volume. These results allow us to rule out that diffusion at this alloy composition is mediated by vacancylike thermal defects, as recently suggested for Zr-rich metal-metal gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…As Cohen and Turnbull already noted [68] the pressure dependence of diffusivity in metallic liquids is much weaker than predicted by the free-volume theory [101,102]. An argument in defense of the free-volume theory for this pressure effect is that the pressure applied externally to the glass does not change the amount of free-volume in the glass, because the glass is already frozen and does not reach the equilibrium state under pressure.…”
Section: Free-volume Mechanismmentioning
confidence: 89%
“…As Cohen and Turnbull already noted [68] the pressure dependence of diffusivity in metallic liquids is much weaker than predicted by the free-volume theory [101,102]. An argument in defense of the free-volume theory for this pressure effect is that the pressure applied externally to the glass does not change the amount of free-volume in the glass, because the glass is already frozen and does not reach the equilibrium state under pressure.…”
Section: Free-volume Mechanismmentioning
confidence: 89%
“…It may not be necessary to consider the atomic size void at all, but it may suffice just to assume that the free volume in metal is small and amounts only to 10 pct of the atomic volume. Indeed the pressure dependence [15,16] and the isotope effect [17] of diffusivity are much smaller than expected for an atomic size free volume. More recently, it was found by computer simulation that atomic diffusion takes place through collective motions (chain reaction) of small local displacements rather than a big step involving free volume.…”
Section: Free-volume Theorymentioning
confidence: 90%
“…In metallic materials, because of the harmonic nature of the interatomic potential, atoms can squeeze through tight space without free-volume when sufficient shear stress is applied. It was demonstrated that diffusivity in metallic liquids is surprisingly insensitive to pressure, whereas in the free-volume theory diffusivity is expected to be suppressed by pressure [36,37]. Lewandowski have shown that the mechanical strength of metallic glasses is almost the same in tension and compression, and thus nearly independent of pressure [38], indicating that pressure has only minor effects.…”
Section: Shear-transformation-zone Modelingmentioning
confidence: 96%